Calcium sulfate‐containing glass polyalkenoate cement for revision total knee arthroplasty fixation. Issue 8 (17th June 2020) - Hasandoost, Leyla; Alhalawani, Adel; Rodriguez, Omar; Rahimnejad Yazdi, Alireza; Zalzal, Paul; Schemitsch, Emil H.; Waldman, Stephen D.; Papini, Marcello; Towler, Mark R.
Abstract: Poly(methyl methacrylate) (PMMA) bone cement is used as a minor void filler in revision total knee arthroplasty (rTKA). The application of PMMA is indicated only for peripheral bone defects with less than 5 mm depth and that cover less than 50% of the bone surface. Treating bone defects with PMMA results in complications as a result of volumetric shrinkage, bone necrosis, and aseptic loosening. These concerns have driven the development of alternative bone cements. We report here on novel modified glass polyalkenoate cements (mGPCs) containing 1, 5 and 15 wt% calcium sulfate (CaSO4 ) and how the modified cements' properties compare to those of PMMA used in rTKA. CaSO4 is incorporated into the mGPC to improve both osteoconductivity and bioresorbability. The results confirm that the incorporation of CaSO4 into mGPCs decreases the setting time and increases release of therapeutic ions such as Ca 2+ and Zn 2+ over 30 days of maturation in deionized (DI) water. Moreover, the compressive strength for 5 and 15 wt% CaSO4 addition increased to over 30 MPa after 30 day maturation. Although the overall initial compressive strength of the mGPC (~ 30 MPa) is less than PMMA (~ 95 MPa), the compressive strength of mGPC is closer to that of cancellous bone (~ 1.2–7.8 MPa). CaSO4 addition did not affect biaxial flexural strength. Fourier transform infrared analysis indicated no cross‐linking between CaSO4 and the GPC after 30 days. in vivo tests are required to determine the effects the modified GPCs as alternative on PMMA in rTKA.